Pengaruh Keterlibatan Ayah terhadap Kecerdasan Emosional Generasi Z - Ela Sabina Devi; Abdul Kadir; Marhani marhani (Indonesian Journal of Educational Counseling, 2026)
This study examines the effect of father involvement on emotional intelligence among Generation Z University students at Universitas Muhammadiyah Palopo. A quantitative approach with a descriptive correlational design was employed, involving 100 respondents aged 18–26 years selected through purposive sampling. Data were collected using questionnaires measuring father involvement (physical and emotional aspects) and emotional intelligence based on Goleman’s five dimensions. The findings indicate that most respondents reported high (48%) and moderate (39%) levels of father involvement, while emotional intelligence was predominantly in the high (45%) and moderate (35%) categories. Pearson correlation analysis revealed a strong and significant positive relationship between Father Involvement and Emotional Intelligence (r = 0.780, p < 0.001). Furthermore, simple linear regression analysis showed that father involvement significantly predicts emotional intelligence (B = 0.276, p < 0.001), accounting for 60.8% of the variance (R² = 0.608). These results suggest that father involvement plays a crucial role in enhancing individuals’ ability to recognize, regulate, and express emotions, as well as to develop healthy social relationships. This study highlights the importance of active paternal engagement in fostering optimal emotional development among Generation Z.